Análise comparativa entre a aquisição dos imóveis financiados e o valor dos aluguéis: um estudo do Programa Minha Casa, Minha Vida - Medeiros, Flaviani Souto Bolzan (2015)
Access to housing is a basic human need. But, on the one hand, the low-income population is struggling to gain access to decent housing, so we need to have this need for state-subsidized home ownership. On the other, Brazil needs to improve the existing housing deficit in the country. A complementary alternative is subsidized rent, because Brazil has many properties that are not engaged in their territory. Thus, it is necessary to advance the implementation of government policies for this purpose, as well as soften the existing housing deficit in the country at the same time, would favor those with lower income. In this sense, this work aims to compare the economic feasibility of acquiring the properties financed by My House My Life Program 2 (MHMLP 2) families with a gross monthly income of R$ 3.275,01 to R$ 5.000,00, with the amount of rent. For this, we applied the Monte Carlo simulation with the help of Crystal Ball® software on properties of R$ 80,000.00, R$ 90.000,00, R$ 110.000.00, R$ 120.000,00, R$ 130.000,00 and also R$ 140.000,00 and R$ 145.000,00 in order to generate the odds and sensitivity analysis in relation to the NPV of both the rent as the purchase in both amortization systems used by MHMLP 2 - Constant Amortization System (SAC) and Price Table - with and without use of resources stemmed from the Fund for Guaranteed Time of Service (FGTS). The results show, that adopting as criteria for choosing the less risk, the best financing option is via SAC without use of FGTS funds. Comparing the NPV of the rent versus the NPV of purchase, in most cases, those properties that have an MRI of 5% to 7%, regardless of the selected depreciation system proved the best options when it comes to funding by MHMLP 2. However, assuming homeowners who have TMA 11% to 15%, with few exceptions, the rent is the best choice.